2010
DOI: 10.1017/s1352465810000020
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Therapy-Relevant Cognitive Capacities in Young People: Development and Psychometric Evaluation of the Self-Reflection and Insight Scale for Youth

Abstract: It appears that the SRIS-Y is a sound instrument for assessing therapy-relevant cognitive capacities in young people, of potential benefit in both research and clinical contexts. Future research foci include the predictive validity of the instrument.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
36
0
10

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(48 citation statements)
references
References 33 publications
2
36
0
10
Order By: Relevance
“…The SRIS has high internal consistency and internal validity (Grant et al, 2002; Roberts and Stark, 2008). The Dutch version of the questionnaire had good psychometric properties (Sauter et al, 2010) and in the current sample, the SRIS-SR and SRIS-IN showed excellent internal consistency (Cronbach's α = 0.94 for SRIS-SR; α = 0.82 for SRIS-IN).…”
Section: Methodsmentioning
confidence: 59%
“…The SRIS has high internal consistency and internal validity (Grant et al, 2002; Roberts and Stark, 2008). The Dutch version of the questionnaire had good psychometric properties (Sauter et al, 2010) and in the current sample, the SRIS-SR and SRIS-IN showed excellent internal consistency (Cronbach's α = 0.94 for SRIS-SR; α = 0.82 for SRIS-IN).…”
Section: Methodsmentioning
confidence: 59%
“…Grant et al (2002) have demonstrated test-retest reliability (r = .75 to .77) and congruent validity with objective measures such as diary keeping, and the scale has been found to be a valid and reliable measure (Roberts & Stark, 2008;Sauter, Heyne, Blote, van Widenfelt, & Westenberg, 2010).…”
Section: Self-reflection and Insightmentioning
confidence: 80%
“…Grant (2003), for example, has examined how coaching influences self-reflection and insight, and other researchers have considered the traits' relevance for readiness for professional development (Roberts & Stark, 2008) and for adolescent populations (Sauter et al, 2010). This applied interest is not surprising in light of the large literature on the clinical relevance of self-conscious traits, particularly private self-consciousness (Ingram, 1990).…”
Section: Discussionmentioning
confidence: 99%
“…To expand upon past work, we emphasized markers of poor functioning, such as anxiety and depression symptoms. Much of the interest in self-reflection and insight comes from clinical, counseling, and coaching domains, particularly areas interested in how introspective abilities may aid or hinder change (e.g., Grant, 2003 andSauter et al, 2010), so it is worth examining how these traits relate to markers of affect and well-being.…”
Section: Introductionmentioning
confidence: 99%